1991
DOI: 10.2105/ajph.81.7.859
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviors, risk factors, and health indicators associated with cigarette use in Mexican Americans: results from the Hispanic HANES.

Abstract: BACKGROUND: Cigarette smokers often engage in other, potentially deleterious, health behaviors. Such behaviors have not been well documented in Mexican American smokers. METHODS: Data from the Southwestern sample of the Hispanic Health and Nutrition Examination Survey (HHANES) were employed to investigate differences in health behaviors, risk factors and health indicators between cigarette smokers and nonsmokers among Mexican Americans. Differences between those smoking less than 10 and 10 or more cigarettes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Other epidemiological studies have shown similar results (e.g. (Breslau 1995;Kendler et al 1993), for different age (Breslau et al 1991;Salive and Blazer 1993) and ethnic (Lee and Markides 1991) subgroups.…”
supporting
confidence: 73%
“…Other epidemiological studies have shown similar results (e.g. (Breslau 1995;Kendler et al 1993), for different age (Breslau et al 1991;Salive and Blazer 1993) and ethnic (Lee and Markides 1991) subgroups.…”
supporting
confidence: 73%
“…In contrast, the results from previous studies of the relationship between higher level of functional decline and smoking have been controversial; some studies have found a significant association between current smoking and functional decline, whereas others did not report, but because the latter studies had small sample sizes and were cross‐sectional, it is possible that these methodological limitations might lead to a “chicken and egg” situation. Smoking is also strongly associated with cancer and cardiovascular diseases, so it is important to educate older adults about smoking cessation.…”
Section: Discussionmentioning
confidence: 93%
“…A variety of factors have been invoked by other authors, including the "healthy migrant" effect, a diet that includes more fruits and vegetables than the typical American diet, and protective psychosocial effects.26'27 However, survey data have shown that many risk factors are not more favorably distributed in US Hispanics, [28][29][30][31][32][33] and Hispanics have more limited access to health care than do Whites.434 It should be recognized, however, that cross-sectional surveys cannot characterize lifetime risk, and important secular trends may be occurring. As demonstrated by the data in this report, the age interaction suggests that conditions affecting younger adult men, notably extemal causes, are not less frequent in Hispanics, and conditions with a long latency, particularly cancer, probably play the predominant role in older individuals.…”
Section: Resultsmentioning
confidence: 99%